From Constitutional Risk Management to Constitutional Risk Management (Emergency Law Misuse) in Hungary - Fruzsina Gárdos-Orosz; Evelin Burján (European Journal of Risk Regulation)
The paper offers a comprehensive overview of Hungary’s emergency law and its misuse over the four years since its introduction in March 2020. Hungary serves as a clear example of how a “state of danger” – initially intended as an exceptional legal measure – can become normalised through repeated declarations. The populist government’s continuous use of emergency powers has led to unchecked lawmaking and the manipulation of legal frameworks to advance populist agendas. The article argues that while Hungary’s detailed emergency provisions in the Fundamental Law were intended to serve as a form of constitutional risk management, after four years of living in a permanent “state of danger”, the scholarly debate has shifted to whether this very risk management has itself become the risk. According to emergency law theory, managing constitutional risks is equally vital in the emergency legal order. Yet in Hungary, both the black letter of the law and the constitutional practices observed during and after the COVID-19 pandemic – along with the Ninth Amendment to the Fundamental Law, which introduced a new emergency regime in 2021 – reveal that constitutional risk management has ultimately failed. This is manifest in the erosion of the separation of powers, the weakening of judicial review, and the shrinking of human rights protections. The article substantiates its argument by examining the related constitutional framework and constitutional practice in Hungary between 2020 and 2024.